The Influence of Price, Product Diversity, Digital Promotion and Place on Consumer Purchase Interest at Shanghai Studio Shops in Batam City - Trisnawati Nasution; Septa Diana Nabella; Ade Sarmini; Sabri Sabri; Mulyadi Mulyadi (Cita konsultindo, 2024)
Batam is a city where quite a lot of people have opened and owned digital printing and offset printing businesses for the needs of consumers in producing their products. So the influence of price, product diversity, digital promotions and place becomes a combination for consumers to determine their purchasing interest. This research was conducted to determine the influence of price, product diversity, digital promotions and location at the Shanghai Studio Store in Batam City. This research uses a causality design with a population of 1 million people. The sampling technique was saturated sampling, totaling 100 people. The data analysis method used is the multiple linear regression analysis method using the SPSS version 25 program. The results of the test show that price, digital promotion and place have no partial effect on consumer buying interest, while product diversity has a partial effect on consumer buying interest. Price, product diversity, digital promotions and place simultaneously have a positive and significant effect on consumer purchase interest.